ASPEK PERTANAHAN DALAM PENGENDALIAN ALIH FUNGSI LAHAN PERTANIAN (SAWAH) - Ahmad Fauzan (Program Studi Agribisnis Fakultas Pertanian, 2012)
Conflict of interest faced by the Goverment with regard to agricultural land confersion is quite dilemmatic. On one side, the regional government has to accelerate economic growth through industry, service and property sector development. On the other side, attention must be given to protect the existence and sustainability of agricultural sector. If such dilemmatic condition is not immediately overcome by developing land policy, it is impossible for agricultural system to survive, as has been indicated by land conversion data in the last three decades. There has been no technology or institutional breakthrough that is able to compensale for agricultural production decrease due to the lost of agricultural lands, especially irrigated fields. Considering such problems, the government has stipulated some provisions in its policy to restrict and or to prevent conversin of fertile lands to non-agricultural uses, one of which is land policy using land allocation arrangements.